Depth of cure, mechanical properties and morphology of dual-cure bulk-fill composites = Profundidad de curado, propiedades mecánicas y morfología de resinas compuestas duales - Sarialioğlu Güngör, Ayça
This study evaluated selected structural and physical properties, such as degree of conversion (DC), Vickers hardness (VHN), and compression strength (CS), of three new dual-cure bulk-fill resin-based composites (RBCs; ACTIVA, HyperFIL, and Fill-Up) and compared them to those of a conventional RBC (Filtek Z250) at three clinically relevant depths. Samples (n=180) were prepared in three depths (2,4, and 6mm). Fourier-transform infrared spectroscopy (FTIR) analysis and VHN and CS tests were performed. The DC value was calculated by considering the relative change in the aliphatic C=C peaks. The fractured surfaces of representative samples were characterized using scanning electron microscopy (SEM). Data were statistically evaluated using two-way analysis of variance and post hoc Bonferroni tests (p<0.05). According to the VHN results, Filtek Z250 showed the highest bottom/top hardness ratio (97.94±1.01) at 2mm thickness and ACTIVA showed the lowest bottom/top hardness ratio (43.48±5.64) at 6mm thickness (p<0.001). According to the FTIR results, the DC decreased with increasing thickness in all materials (p<0.05). Filtek Z250 showed the highest (301±12.4 MPa) and ACTIVA exhibited the lowest (232±17.2 MPa) CS values at 2mm thickness (p<0.05). The lowest CS values were obtained for ACTIVA, and the highest values were obtained for Filtek Z250 for samples with thicknesses of 4 and 6mm, respectively (p<0.05). The structural features of restorative composites, such as the resin chemistry and filler type and content, and the operational parameters (i.e., material thickness and curing conditions) strongly affect crosslinking reactions and thus the DC, VHN, and CS values.